Pengaruh Karakteristik Wirausaha, Motivasi, Pengalaman, Kemampuan Usaha Terhadap Keberhasilan Usaha pada UMKM Olahan Ikan di Pesisir Dusun Watu Ulo, Desa Sumberejo - Dian Septi Riski Illahi; Santoso, Budi; Reskiputri, Tatit Diansari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Fish-processing MSMEs (Micro, Small, and Medium Enterprises) in the coastal area of Dusun Watu Ulo, Sumberejo Village, play a strategic role in supporting the local economy and utilizing the abundant potential of marine resources. However, not all MSME actors are able to achieve equal business success, despite operating within a relatively similar resource ecosystem. This indicates that business success is largely influenced by internal factors of the entrepreneurs themselves. This study aims to analyze the influence of entrepreneurial characteristics, motivation, experience, and business capability on the business success of fish-processing MSMEs in the region. The research approach employed is quantitative, using a survey method involving 60 MSME actors selected through simple random sampling, and analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that simultaneously, the four independent variables have a significant effect on business success. Partially, business capability has the most dominant influence, followed by motivation and experience, while entrepreneurial characteristics, although positive, are not statistically significant. These findings highlight the importance of enhancing the managerial and technical capacities of MSME actors to improve business success in the coastal fish-processing sector.